Acupuncture and related techniques for type 2 diabetes mellitus: A systematic review protocol. Issue 2 (January 2019) - Liu, Meilu; Chen, Jianrong; Ren, Qing; Zhu, Weifeng; Yan, Dongmei; Nie, Heyun; Chen, Xiaofan; Zhou, Xu
Abstract: Background: Type 2 diabetes mellitus (T2DM) is a major global health problem. As a complementary treatment, acupuncture and related techniques are widely used to treat metabolic and endocrine diseases, but their efficacy and safety for T2DM are yet to be established. This systematic review will qualitatively and quantitatively summarize the current randomized controlled trial (RCT) evidence regarding the efficacy and safety of acupuncture and related techniques in patients with T2DM. Methods: Comprehensive literature searches will be performed on PubMed, Embase, Cochrane Central Register of Controlled Trials, and a trial registry "ClinicalTrials.gov" from inception to December 3, 2018. We will include RCTs for patients with T2DM that compared acupuncture with placebo, antidiabetic drugs, lifestyle interventions, or the combination. Primary outcomes are fasting blood glucose and hemoglobin A1c. Secondary outcomes include 2-hour blood glucose, fasting insulin, homeostatic model assessment for insulin resistance, incidence of diabetic complications, and acupuncture-related adverse events. The risk of bias of the RCTs included in the review will be examined using a revised Cochrane handbook tool. Heterogeneity will be detected using Cochran Q test and I 2 statistics. With the use of random effects model, we will perform meta-analyses to pool results of RCTs. The effect measures will be weighted or standardized mean difference with 95% confidence intervals (CIs) for the continuous outcomes and risk ratio with 95% CIs for the dichotomous outcomes. Subgroup analyses and meta-regression with predefined effect modifiers will be performed to explore the sources of heterogeneity. Where appropriate, we will assess the possibility of reporting bias based on funnel plots and quantitative detection. We will appraise the quality of evidence using the Grading of Recommendations Assessment, Development, and Evaluation system for each outcome. Results: This study will provide accurate results and balanced inferences on the efficacy and safety of acupuncture and related techniques on T2DM. Conclusion: This well-designed systematic review will establish high-quality evidence of the efficacy and safety of acupuncture and related techniques for T2DM to facilitate the clinical practice and guideline development. PROSPERO registration number: CRD42018115639.